The Coaching of Dunia Coding Program to Improve Computational Thinking Ability at As Shofa Junior High School Pekanbaru : Pembinaan Program Dunia Coding untuk Meningkatkan Kemampuan Computational Thinking Pada SMP As Shofa Pekanbaru - Indah Lestari; Satria Perdana Arifin; Yohana Dewi Lulu Widyasari; Muhammad Mahrus Zain; Heni Rachmawati (Universitas Lancang Kuning, 2023)
Computational thinking (CT) is basic competency that must be provided to Indonesia's young generation, through integration into curriculum or extracurriculars to face the information, industrial era 4.0 or society 5.0. SMP As Shofa Pekanbaru has computer extracurriculars, but the material is only Office. This school needs programming extracurricular coaching which can be mediafor training students' CT. Therefore, in this community service program, extracurricular programming training was carried out at SMP As Shofa, namedDunia Coding. This activity produced 2 textbooks. The implementation method is an offline workshop in 12 meetings 1x/week. The results obtained were that 73.9% of students agreed that the material provided was very appropriate to their needs, 82.6% of students agreed that the program was very useful, 80.4% of students agreed that the delivery of the material was very clear, interesting, and easy to understand, and 56.5% of students agreed that the implementation time was sufficient